CONTRIBUTE TO STUDENTS THROUGH THE WEBINAR "HOW TO SELF DEVELOPMENT AND MANAGING TIME EFFECTIVELY" - Genoveva Genoveva; Putri Cantika; Agung Panglima P.Lodong; Sely Oktavia; Vivien L. Iskandar (Rural Development For Economic Resilience (RUDENCE), 2021)
Abstract This community service activity is our contribution to students carried out during the covid-19 pandemic, so that it is in the form of online. Based on the results of a survey of 5 high schools and 5 universities in the Jabodetabek area, there are six webinar materials expected by students. From the six materials, two materials with the highest needs were selected, namely Self Development and Time Management. The next step is to arrange the outline of material and find the speaker from the millennial circle, to match the participants who are senior high school and university students. The webinar held on July 3, 2021, which was attended by 184 participants. Feedback is carried out to find out the benefits and effectiveness of choosing topics and speakers. Internally, the advisor also evaluates the activities with the students involved in these activities. The webinar can run smoothly and get positive feedback from participants.